Diagnosis, Management and Complication of Tuberculosis: A Comprehensive Systematic Review - Restu Wulandari; Magdalena Corry Mega Christin (International Medical Journal Corp. Ltd, 2025)
Background: The study aims to evaluate current evidence on diagnostic approaches, treatment strategies, and complications associated with Tuberculosis (TB), highlighting the need for further research and understanding due to nonspecific clinical presentation and limited diagnostic tools, and the potential for complications from both disease process and treatment. Methods: This systematic review complied with PRISMA 2020 guidelines and concentrated solely on full-text articles published in English from 2015 to 2025. Editorials and review articles lacking a DOI were excluded to maintain the integrity of high-quality sources. A literature study was performed using reputable databases such as ScienceDirect, PubMed, and SagePub to identify pertinent studies. Result: The initial database search produced more than 8000 pertinent publications on the subject. After a thorough three-stage screening process, eight papers fulfilled the inclusion criteria and were chosen for detailed study. Each study underwent a meticulous critical evaluation, facilitating a comprehensive grasp of the diagnosis, management, and complications of tuberculosis. This systematic approach ensured that the analysis was based on high-quality evidence, aligned with the study's objectives, and was capable of yielding significant insights into this complex relationship. Conclusion: Treatment for tuberculosis requires accurate diagnosis and effective management to prevent complications. Advances in molecular diagnostics and emerging therapies offer hope for treatment, but barriers like limited access and late diagnosis hinder control efforts. Strengthening diagnostic capabilities and addressing socioeconomic determinants are crucial for improving patient outcomes.